Production and Maturation of Soaps with Non-Edible Fermented Olive Oil and Comparison with Classic Olive Oil Soaps - Antonio Ferracane; Alessia Tropea; Fabio Salafia (Fermentation, 2021)
The study reports the alternative use of non-edible fermented olives for the production of high-quality natural soaps with a fast production process, low environmental impact, and without preliminary treatments for the raw material. Damaged olives, not used as food, were fermented naturally and the oil was extracted by mechanical extraction. The product obtained was not for human consumption due to its high acidity, but it had a low content of peroxides. The non-edible olive oil obtained and an extra virgin olive oil, produced from the same olive cultivar, were subjected to saponification with sodium hydroxide. The soaps were produced with complete (0% of non-neutralized fatty acids) and incomplete (5% of non-neutralized fatty acids) saponification; the amount of sodium hydroxide to be used was determined with the saponification index. The soaps were aged for six months by monitoring pH, color, and behavior in an aqueous solution. The results show that the olives’ fermentation improves and speeds up the soap production and maturation process since the oil obtained from fermented non-edible olives is more suitable for the saponification process than the oil obtained from non-fermented edible olives. Non-edible fermented olives can be used for obtaining natural and high-quality soaps, reusing drupes classified as food waste.